2013
DOI: 10.2298/mpns1306233t
|View full text |Cite
|
Sign up to set email alerts
|

Systemic multimodal approach to speech therapy treatment in autistic children

Abstract: By applying the systemic multimodal approach when dealing with autistic children and by comparing their achievements on tests applied before, during and after the application of this mode, it has been concluded that certain improvement has been achieved in the functionality within the diagnosed category. The results point to a possible direction in the creation of new methods, plans and programs in dealing with autistic children based on empirical and interactive learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…This leaves a high number of children without adequate intervention from an early age, which reduces the chances of achieving better results. The duration and frequency of intervention are directly related to its effects on the children's cognitive and social emotional development, as well as on their health status [31,32]. In our study group, the duration and frequency of treatment was far below the time proved to be effective in the Perry preschool program, which included 5 hours a day, five days a week.…”
Section: Discussionmentioning
confidence: 97%
“…This leaves a high number of children without adequate intervention from an early age, which reduces the chances of achieving better results. The duration and frequency of intervention are directly related to its effects on the children's cognitive and social emotional development, as well as on their health status [31,32]. In our study group, the duration and frequency of treatment was far below the time proved to be effective in the Perry preschool program, which included 5 hours a day, five days a week.…”
Section: Discussionmentioning
confidence: 97%
“…Such a naturalistic approach to speech interventions has been shown to be effective not only in the therapy room, but also at home in cases where parents receive training in these methods 37 . Therefore, this has led researchers to advocate for a systemic multimodal approach to language therapy interventions in individuals with ASD 38 . While developing language skills in multiple settings has proved to be important, other works have also indicated that continuing sessions with a single therapist can be more effective than switching practitioners over time 39 .…”
Section: Speech/language Therapymentioning
confidence: 99%